Production and Quality Evaluation of Paste Made from Two Jawa Date Cultivars - S. Bushra, Eshrag; E. Sulieman, Abdel Moneim; Aburigal, Amna A. A.; Modawi, Hassan A. (Gezira Journal of Engineering and Applied Sciences, 2018)
The objective of the present work was to study the production of paste from the local Sudanese date cultivars namely; red Jawa and black Jawa. The date fruit samples were subjected to physical and chemical analysis before production of the paste. The chemical, microbiological and sensory characteristics of date paste were evaluated after processing. The results indicated relative increasing of moisture content in the red Jawa paste (RJP) 23.34% as compared with black Jawa paste (BJP) 20.35%, the ash content in the (RJP) and (BJP) were 1.15% and 1.09%, respectively. Protein content in the (RJP) and (BJP) were 1.75% and 2.04%, respectively. The total soluble solid in (RJP) and (BJP) were found to be 71.5% and 73.9, respectively. The titrable acidity in (RJP) and (BJP) were found to be 0.31% and 0.41% respectively. The pH values were found to be 5.13 and 5.35 in (RJP) and (BJP), respectively. The microbial analysis of date paste showed low levels of total microbial load. The sensory evaluation indicated that all the paste samples were highly accepted by panelists. The study recommended utilization of low quality date fruits like Jawa in production of various products to increase its economic value.